SOSIALISASI TENTANG PEMBERLAKUAN UPAH TENAGA KERJA DI BAWAH STANDAR MINIMUM DITINJAU DARI PP NO. 36 TAHUN 2021 TENTANG PENGUPAHAN DAN HUKUM ISLAM DI DESA MEDAN KRIO - Nurhayati, Siti; Wahyuni, Emi; Hasibuan, Syaiful Asmi (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
The goal to be achieved from this service is to increase community understanding and knowledge, especially in Medan Krio Village, Deli Serdang Regency, through counseling and socialization regarding the implementation of labor wages below the minimum standard that distinguishes the concept of wages in Government Regulation Number 36 of 2021 concerning Wages and Islamic law. This is very important because Islam has its own distinctive view of the discussion of ijarah (wages) and the concept offered is more of a sense of justice and benefit in order to fulfill each other's lives between workers and employers for the benefits obtained, although in its implementation it has fulfilled two of the three principles of remuneration in Islamic law, namely the principle of justice and pleasure, the principle that has not been fulfilled is the principle of worthiness. This really needs to be conveyed to the community, especially the people in Medan Krio Village, where the majority of education is only up to high school so that they have the principle of only getting a job without thinking about their rights as workers which have been regulated in applicable laws and regulations.